Contribution of GO System Glycosylases to Mutation Prevention in Caulobacter crescentus. (10th October 2019) - Fernández‐Silva, Frank S.; Schulz, Mariane L.; Alves, Ingrid Reale; Freitas, Rubia R.; da Rocha, Raquel Paes; Lopes‐Kulishev, Carina O.; Medeiros, Marisa H. G.; Galhardo, Rodrigo S.
Abstract : 8‐oxo‐7, 8‐dihydroguanine, commonly referred to as 8‐oxoG, is considered one of the most predominant oxidative lesions formed in DNA. Due to its ability to pair with adenines in its syn configuration, this lesion has a strong mutagenic potential in both eukaryotes and prokaryotes. Escherichia coli cells are endowed with the GO system, which protects them from the mutagenic properties of this lesion when formed both in cellular DNA and the nucleotide pool. MutY and MutM (Fpg) DNA glycosylases are crucial components of the GO system. A strong mutator phenotype of the Escherichia coli mutM mutY double mutant underscores the importance of 8‐oxoG repair for genomic stability. Here, we report that in Caulobacter crescentus, a widely studied alpha‐proteobacterium with a GC‐rich genome, the combined lack of MutM and MutY glycosylases produces a more modest mutator phenotype when compared to E. coli . Genetic analysis indicates that other glycosylases and other repair pathways do not act synergistically with the GO system for spontaneous mutation prevention. We also show that there is not a statistically significant difference in the spontaneous levels 8‐oxodGuo in E. coli and C. crescentus, suggesting that other yet to be identified differences in repair or replication probably account for the differential importance of the GO system between these two species. Environ. Mol. Mutagen. 61:246–255, 2020. © 2019 Wiley Periodicals, Inc.